Interactive maps. Tools for citizen participation - Medranda Morales, Narcisa (2018)
Interactive maps are digital tools that make information available to people in a visual way, in a single set. In addition, they offer the necessary flexibility so that each person can access the information of their interest. These characteristics make these maps an optimal tool to promote citizen participation. A successful example of the use of these maps as a tool to encourage citizen participation is the Mapa Infoparticipa Project, which,with these tools, socializes the transparency levels of local governments in countries such as Spain, Ecuador, Colombia, Chile and Brazil. This article presents what interactive maps are and argues how they are a tool to encourage citizen participation, based on the experience of Mapa Infoparticipa Project.